Development and analysis of two bioaugmentation approaches: a volatile organic compound bioaugmentation case and a pentachlorophenol bioaugmentation case - Zou, Yulan (2017)
Bioaugmentation (i.e. introduction of microorganism with specific metabolic capacity that can enhance biological processes) as a cost-effective method for remediation of environmental pollutants, has gained popularity over the decades. One of the most challenging concerns in the use of this technology is the sustainability of the bioaugmentation system. In this project, we aimed to develop two co-culture bioaugmentation systems to achieve satisfactory efficiency and sustainability for two biotechnological applications (one aerobic and the other, anaerobic), using differing approaches. In the first approach, members of the bioaugmentative consortium to be developed were drawn from a previously analyzed pool of isolates from a two-liquid phase partitioning bioreactors (TPPBs) handling volatile organic compound (VOC) removal. After multidimensional characterization of 26 candidate strains, one finial consortium with outstanding VOCs’ removal capacity was formulated by 12 out of the 26 strains. Two methods of testing the bioaugmentation efficiency were developed after this consortium was formulated. In the first method, the consortium’s removal efficiency was tested within an enclosed environment in an air purification device, which reaches 100% removal of formaldehyde. The second method is colorimetric in nature, measuring formaldehyde concentration dissolved in aqueous medium. The bioaugmentative consortium’s formaldehyde removal efficiency can be maintained within the range of 80%-100% over at least 16 days under settings allowing for random environmental perturbation. Microbial interaction among strains in this formulation of co-culture was briefly assessed under 2strain co-culture setting. In the second approach, activated sludge from local wastewater treatment plant was used as the start-up seed of anaerobic bioreactors and bioaugmentative consortia were developed to remove refractory compounds that may negatively impact the anaerobic wastewater treatment process. The composition of the consortia were left uncharacterized while development was going on. After acclimatization of the activated sludge to pentachlorophenol (PCP) and its metabolic intermediate separately over one year, each bioaugmentative consortium and several mixtures’ PCP removal efficiency and biogas production were tested. The potential bioaugmentative sludges were put through a dilution scheme and heat treatment to reduce the complexity of the consortia for more regulated usage in the future. Several mixtures were made with the subcultures of these simplified consortia. Their bioaugmentation efficiency was tested by High-Performance Liquid Chromatography (HPLC), and one mixture of the subculture revealed 76.1% of PCP removal. In the process of developing bioaugmentative consortia, relevant microbial dynamics were preliminarily reviewed through denaturing gradient gel electrophoresis (DGGE), but found not to be appropriate or sufficient in depth to reveal useful information. Two recent advances in techniques – microfluidic q-PCR and pyrosequencing – were preliminarily explored for application in microbial population tracking and bacterial interaction investigation.